The Study of Analysis Toward Zakat of Honey on Mazhab Imam Syafi’i Perspective - Harahap, Haddad Ulum; Putra, Dedisyah; Khalidi, Muhadi; Linur, Rahmat; Acela, Nuriza (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2023)
Honey is a special food ingredient because of its taste, nutritional value and high efficacy. That's why honey is revered by many people as a unique type of food that is also medicinal which has been known since ancient time because it is able to maintain the immune system for those who consume it. In the past, people were not familiar with honey livestock and only got it in forests, but now many people have cultivated honey and even developed it with a factory processed system in such a way. This research will discuss the position of honey and the law of zakat on the results of the honey business based on the thought of mazhab (school of thought concerning Muslim law) Imam Shafi'i. This research is a library research with a qualitative approach. The result of research was that Imam Syafi’I had two views known as Qaul al-Qadim and Qaul al-Jadid. Zakat of honey in qaul al-qadim is obligated to pay zakat with qiyas that honey included staple food based on hadist and prophet’s friends. Imam Syafi’I says that honey is not obligated to pay because it does not include staple food. Imam Syafi'i moved from qaul qadim to qaul Jadid because he found a stronger argument to be used as a legal basis. Therefore, Imam Syafi'i did ijtihad and dismantled the results of the previous ijtihad be based on weak arguments. He says “The hadith saḥiḥ is my mazhab and leave my opinion if it contradicts the hadith sahih”. Istinbath (method in understanding the proposition of revelation)of law used by him is Imam Syafi’I to construct the reason based the hadist. Keywords: Honey, Zakat, Imam Syafi’i